Immediate loading with single-piece implant following extraction - Hemlata Dwivedi; Rita Jain (Indian Journal of Dental Sciences, 2017)
Although dental implantology had evolved over a number of years, many dental surgeons are unaware of the concept of immediate loading with the use of one-piece implant that began in the early 1960s. The goal of successful prosthodontics rehabilitation is to provide function, esthetics, and comfort to the patient. The aim of this literature is to provide an overview of one-piece implant, with its advantages and disadvantages over conventional two-piece implant. Immediate prosthetic of a one-piece system allows for a better tissue healing and better adhesion of gingival mucosa to form a collar which is healthy and adherent to the implant, avoiding a second surgical procedure, and also includes a very important aspect esthetics. This article describes a case report of immediate loading with single-piece implant following extraction.